Legacy and emerging organophosphorus flame retardants and plasticizers in indoor microenvironments from Guangzhou, South China - Tang, Bin; Christia, Christina; Malarvannan, Govindan; Liu, Yin-E.; Luo, Xiao-Jun; Covaci, Adrian; Mai, Bi-Xian; Poma, Giulia (Environment international, 2020)
[Display omitted] •PFRs, ePFRs, LPs, and APs were investigated in dust and air from bedroom and offices.•Different types of dust showed specific levels and patterns for each group of chemicals.•A/Cs were the main source of PFRs/ePFRs, and high levels of LPs/APs were found in floor dust.•Levels in dust and air correlated for chemicals with log Koa < 14.•Dust ingestion was the main human exposure route to these chemicals in South China. Indoor dust has been extensively used for assessment of indoor contamination, especially for semi-volatile organic compounds (SVOCs). In the present study, the occurrence of four groups of SVOCs, i.e. organophosphorus flame retardants (PFRs), emerging PFRs (ePFRs), legacy phthalates (LPs), and alternative plasticizers (APs), was investigated in the indoor dust and air collected from floors, table surfaces, windows, and air conditioner (A/C) filters in bedrooms and offices in Guangzhou, South China. In bedrooms, A/C filter dust showed the highest median concentrations of PFRs (4670 ng/g) and ePFRs (586 ng/g), whilst the highest median concentrations of LPs and APs were found in floor (240,880 ng/g) and window dust (157,160 ng/g), respectively. In offices, A/C filter dust showed the highest median concentrations for PFRs (6750 ng/g) and APs (504,520 ng/g), while the highest ePFR median level was found in PC table dust (5810 ng/g) and LPs in floor dust (296,270 ng/g). Median air concentrations of PFRs, ePFRs, LPs, and APs were measured at 4.6, 0.12, 399, and 25 ng/m3 in bedrooms, and at 8.0, 0.05, 332, and 43 ng/m3 in offices, respectively. Tris(1-chloro-iso-propyl) phosphate (TCIPP) was the predominant PFRs/ePFRs in both dust and air. Di(2-ethylhexyl) phthalate (DEHP), di-iso-decyl phthalate (DIDP) and di-iso-nonyl phthalate (DINP) were the main LP/AP compounds in dust, whilst di-iso-butyl phthalate (DIBP) and di-n-butyl phthalate (DNBP) were the most abundant LPs/APs in air. A significant correlation (p < 0.05) was found between dust and air levels for chemicals with log Koa < 14, indicating that equilibrium was achieved for these chemicals but not for those with log Koa > 14. Among the investigated human exposure pathways (i.e. dust ingestion, dermal absorption, and air inhalation), dust ingestion was the predominant one for all chemicals. Human exposures of this magnitude to these chemicals through the investigated pathways was unlikely to present a health risk in the present study.